The effectiveness of interventions addressing loneliness in older persons: An umbrella review. (2020) - Jarvis, Mary-Ann; Padmanabhanunni, Anita; Balakrishna, Yusentha; Chipps, Jennifer
Abstract: Ageing is associated with social isolation and loneliness and can have deleterious effects on older persons' mental and physical well-being. Several systematic reviews and meta -analyses have been published on interventions addressing loneliness and social isolation among older persons living in the community or residential care. The present study is an umbrella review of systematic reviews and meta -analyses targeting loneliness in older persons living in community/residential care settings using an adapted Joanna Briggs umbrella review methodology. A systematic electronic search of 12 databases was conducted using search terms synonymous with aged, intervention, social isolation, loneliness, and systematic review for the period 2000–2017. Two reviewers independently screened and selected relevant reviews and assessed the quality of the reviews using the AMSTAR 2. Sixteen reviews of varying quality were identified and included. The 16 reviews focused on eInterventions, non-eInterventions or interventions including both. Due to the heterogeneity of both the reviews, and the included primary studies, the primary studies within the reviews meeting the study criteria were extracted and classified according to the focus of the intervention. Nineteen unique RCT primary studies were extracted and effect sizes calculated for 14 RCTs for outcome scales and different modes of offering interventions addressing loneliness in older persons. There was limited effect on loneliness with effect sizes ranging from −1.23 (CI95 −1.67, −0.78) to 0.44 (CI95 0.13–0.76) with the greatest effect size in a social cognition intervention. The outcome suggests that both high quality reviews with greater homogeneity and homogenous primary studies in loneliness are required.